CRIMINAL POLICY AGAINST ELE CTRICITY THEFT AT PT. PLN ULP KABANJAHE KARO REGENCY - Doni Eperata; Marsella; Nanang Tomi Sitorus (SUAN PUBLISHER, 2024)
This study aims to determine the crime factors of electricity theft at PT PLN ULP Kabanjahe, Karo Regency, and to find out what efforts and countermeasures are made by PLN against electricity theft. This research was conducted at PT PLN ULP Kabanjahe.The resources obtained were from visits to the Kabanjahe PLN research site. Data collection techniques used are interviews and to the field used to analyze research results.The results obtained / obtained from this study include that, the factor of the crime of theft of electricity at PT. PLN ULP Kabanjahe is caused by several factors, namely environmental factors and economic factors where the influence of weak economic pressure encourages the perpetrator to commit the crime of theft of electric current, factors of public ignorance of sanctions and fines imposed on the thief of electric current. The efforts made by PLN in preventing and overcoming the crime of theft of electricity flow are conducting checks once a month with strict supervision by P2TL, as well as providing direction to the community and giving large sanctions / fines to violators.